Comparative analysis of Turkey's environmental performance with Eastern European countries according to international EPI 2022 data - Karahan, Mehmet; Yildirim, Zafer; Yildirim, Turgay (Keai Publishing Ltd, 2025)
In order to effectively address environmental issues, it is important for governments to identify the problems causing environmental pollution within their scope and to develop appropriate solution policies. In order to identify environmental problems and develop necessary policies, it is necessary to consider the environmental performance of countries. Therefore, measuring the environmental performance of countries is of great importance. One of the prominent indices in measuring environmental performance today is the Environmental Performance Index (EPI) developed by Yale University. The main purpose of EPI is to quantitatively measure and compare the environmental performances of countries in order to monitor their progress in environmental sustainability. As of 2022, EPI consists of three main criteria: climate change, environmental health, and ecosystem vitality. In this study, Turkey's environmental performance was evaluated using the Entropy-based PROMETHEE method with international EPI 2022 data. Subsequently, the environmental performances of Turkey and other Eastern European countries were compared in terms of criterion superiority to determine their strengths and weaknesses. In this context, various sub-criteria were analyzed under main criteria such as climate change mitigation, air quality, sanitation and drinking water, heavy metals, waste management, biodiversity and habitat, ecosystem services, fisheries, acid rain, agriculture, and water resources. As a result of the analysis conducted as of 2022, it emerged that Turkey generally exhibited weak environmental performance among Eastern European countries and there is a need for improvement in each criterion. Giving priority to criteria such as Climate Change Mitigation, Sanitation and Drinking Water, Biodiversity and Habitat, Fisheries, and Acid Rain, in which Turkey obtained the lowest scores in the ranking, would be a more strategic approach.
Keywords: Environment; Environmental performance; Environmental Performance Index; EPI